2014 Joint Report on Multilateral Development Banks' Climate Finance - African Development Bank (World Bank, Washington, DC, 2015)
This joint report on MDB Climate Finance captures a particular context of activities that Multilateral Development Banks (MDBs) carry out in developing and emerging economies. The context is built on the premise that development finance is being provided in a world shaped by climate change. This is the fourth edition of the Joint Report on MDB Climate Finance. The report covers financing for climate change mitigation and adaptation projects and activities, in developing and emerging economies, committed by this group of MDBs in 2014. The report contains the following new information, not presented in previous years: overview of MDB climate finance from 2011 to 2014; information about the financial instruments used by MDBs for climate finance; and additional thematic regional coverage, including small island states and least developed countries. This report has two main sections. Section 1 contains total MDB climate finance numbers for 2014, broken down by adaptation and mitigation and by sector and geographic region, as well as MDB climate finance since 2011. Section 2 provides explanations on the MDB joint approach: definitions, geographical coverage, and sectoral breakdown. It also contains a guidance section and provides case studies to illustrate the MDB adaptation and mitigation finance tracking approach. Annexes A to C provide additional information and numbers on A) Finance with dual, adaptation and mitigation, benefits; B) Financial instruments used by MDBs for climate finance; and C) MDB mitigation finance outside of the Joint Methodology. This report does not cover public or private capital mobilized by MDB climate finance. A parallel group is working on the development of a harmonized methodology to be used toward that end.